Perbandingan Aktivitas Katalis Dolomit dan Batu Kapur Lokal dengan Katalis Nikel Komersial untuk Dekomposisi Toluen sebagai Model Tar - Herri Susanto; Aisyah Ardy (Jurnal Teknologi Bahan dan Barang Teknik, 2016)
Tar content will cause problem during utilization of producer in internal combustion engine. Our research deals with the development tar cracking process for optimum elimination of tar from gaseous product of gasification. Locally available minerals were used as catalyst, i. e: dolomite and lime stone obtained from minings in Padalarang and Blitar respectively. Experiments were carried out in a tubular reactor having an inside diameter of 2.54 cm and a total length of 33.5 cm. The amount of catalyst in the reactor was 10 gram and the particle size was 16/18 mesh. The gas stream containing tar was modeled with toluene vapour in N2 stream with a toluene concentration of 0.002- 0.004 g/L and gas flow rate of 32-38 L/h. Reactor temperature was adjusted at 500, 600, dan 700oC. The progress of tar cracking was observed using the toluene concentration at the gas inlet and the outlet of the reactor. Highest toluene conversion was found 86% during cracking on dolomite at 700oC without the presence of steam in the gas stream. For comparison, our experiments using Ni-based steam reforming catalyst resulted a toluene conversion of about 85%. This figure was relatively lower than those of dolomite and limestone. Catalytic activity of dolomite for toluene was about 0.084 mgtoluene/(gcat.min) and that of limestone was 0.01-0.05 mgtoluene/(gcat.min). We also found that toluene might undergo cracking without any catalyst at a temperature of 700oC. This condition was similar to the oxidation  zone in a downdraft gasifier.Kandungan tar akan menyebabkan masalah jika gas produser hasil gasifikasi biomassa digunakan sebagai bahan bakar alternatif di dalam internal combustion engine. Penelitian ini ditujukan untuk mengembangkan katalis penyisihan tar secara optimal dari gas produser. Mineral lokal yang digunakan sebagai katalis adalah dolomit dan batu kapur yang merupakan hasil penambangan dari Padalarang dan Blitar. Percobaan dilakukan dalam sebuah reaktor pipa dengan diameter dalam 2,54 cm dan panjang total 33,5 cm. Jumlah katalis yang digunakan adalah 10 gram dengan ukuran 16/18 mesh. Gas produser dimodelkan oleh uap toluen dengan konsentrasi 0,002-0,004 g/L dan laju alir gas N2 32-38 L/jam yang diukur pada suhu kamar. Temperatur reaktor ditetapkan 500, 600, dan 700oC. Kinerja proses perengkahan tar diamati melalui konsentrasi toluen masuk dan keluar reaktor perengkahan tar. Konversi toluen tertinggi adalah 86% dengan menggunakan katalis dolomit pada temperatur 700oC tanpa menggunakan steam. Sebagai perbandingan, penelitian dengan menggunakan katalis nikel menghasilkan konversi toluene sekitar 85%. Kemampuan katalitik dolomit untuk mengkonversi toluen adalah 0,084 mgtoluen/(gkat.menit) sedangkan batu kapur adalah 0,01-0,05 mgtoluen/(gkat.menit). Perengkahan toluen dapat dilakukan tanpa menggunakan katalis temperatur 700oC. Kondisi ini sama dengan zona oksinasi pada downdraft gasifier.